1998
DOI: 10.1038/bjc.1998.81
|View full text |Cite
|
Sign up to set email alerts
|

The association between naevi and melanoma in populations with different levels of sun exposure: a joint case-control study of melanoma in the UK and Australia

Abstract: Summary Two case-control studies were set up to investigate the relationship between melanocytic naevi and risk of melanoma and to compare the naevus phenotype in two countries exposed to greatly different levels of sun exposure and different melanoma rates. In England 117 melanoma cases and 163 controls were recruited from the North-East Thames Region and 183 melanoma cases and 162 controls from New South Wales, Australia. Each subject underwent a whole-body naevus count performed by the same examiner in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 29 publications
3
69
0
3
Order By: Relevance
“…Whether longer telomeres also influence other skin phenotypes remains to be determined. However, it has been observed that both the ''moley'' phenotype and the ''sun damage'' phenotype (with solar elastosis and solar keratoses), which are both associated with an increased risk of melanoma, are often mutually exclusive (38,39). It is therefore possible that longer telomere length delays senescence in keratinocytes and fibroblasts so patients with higher nevus counts may display less photoaging.…”
Section: Discussionmentioning
confidence: 99%
“…Whether longer telomeres also influence other skin phenotypes remains to be determined. However, it has been observed that both the ''moley'' phenotype and the ''sun damage'' phenotype (with solar elastosis and solar keratoses), which are both associated with an increased risk of melanoma, are often mutually exclusive (38,39). It is therefore possible that longer telomere length delays senescence in keratinocytes and fibroblasts so patients with higher nevus counts may display less photoaging.…”
Section: Discussionmentioning
confidence: 99%
“…In a longitudinal comparison of Scottish and Australian children followed from birth, Australian children experienced a rapid increase in MN counts in their second year of life whereas children raised in the contrasting UVR environment of Scotland showed a delay of f12 months (11). It is interesting to note that there is little difference in the MN counts of older Caucasians from diverse UV environments (7,37,38), despite the consistent differences in melanoma incidence (39,40). These findings suggest that interventions in very young children are necessary to prevent the early onset of MN and melanoma later in life.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, melanomas developing on the trunk via the intermittent UVR (non-CSD) pathway tend to have relatively earlier age of onset and are associated with higher naevus count. Several studies have published findings concordant with the divergent pathway hypothesis (Carli and Palli, 2003;Chang et al, 2009;Bataille et al, 1998). Given the strong association between truncal (non-CSD) melanomas and naevus development, and the fact that most naevi carry BRAF mutations (Pollock et al, 2003), it is not surprising that the non-CSD melanomas also tend to carry BRAF mutations (reviewed in .…”
Section: The Divergent Pathway Model Of Melanomamentioning
confidence: 51%